2007
DOI: 10.1111/j.1442-2042.2007.01776.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper urinary tract recurrence following radical cystectomy for bladder cancer

Abstract: Aim:The objective of this study was to analyze the clinicopathological features of upper urinary tract recurrence following radical cystectomy for bladder cancer. Methods: Between 1995 and 2003, 583 patients underwent radical cystectomy and urinary diversion for bladder cancer at the authors' institution and the related hospitals. A retrospective review of patient records was carried out to evaluate characteristics of patients who underwent upper urinary tract recurrence after radical cystectomy. Results: Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 12 publications
2
17
0
8
Order By: Relevance
“…In this study, the median follow-up period was 53 months (13–207 months), which was not quite a long enough period of time for follow-up of UUTR in reference to 10–15 years. However, it might be cautiously said that this study may be representative for RC with an acceptable time of follow-up of UUT, because most of our RC patients (approximately 80%) had completed their follow-up with more than postoperative 36–44 months, and most previous reports also showed a median time of follow-up period of between 30–50 months [3], [6], [8], [23]. Therefore, with our median follow-up period, it was worth discussing the natural histories of 11 UUTRs, although conduct of further studies with large numbers of subjects with further long-term follow-ups would be necessary in order to obtain more clinical significance for comparison with other studies.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this study, the median follow-up period was 53 months (13–207 months), which was not quite a long enough period of time for follow-up of UUTR in reference to 10–15 years. However, it might be cautiously said that this study may be representative for RC with an acceptable time of follow-up of UUT, because most of our RC patients (approximately 80%) had completed their follow-up with more than postoperative 36–44 months, and most previous reports also showed a median time of follow-up period of between 30–50 months [3], [6], [8], [23]. Therefore, with our median follow-up period, it was worth discussing the natural histories of 11 UUTRs, although conduct of further studies with large numbers of subjects with further long-term follow-ups would be necessary in order to obtain more clinical significance for comparison with other studies.…”
Section: Discussionmentioning
confidence: 93%
“…For decades, the schedule and methods for surveillance of UUT after RC have been discussed because of its characteristics of low prevalence (0.7–7.4%) [3], [7], [8], [12], [20][22], late diagnosis after postoperative 25–40 months [6], [7], [23], poor prognosis with a median survival of 10–20 months from diagnosis [6], [23], difficulty in detection of abnormal UUT findings in the changed abdomino-pelvic anatomy with diverted intestinal urinary tract of urinary diversions, and contaminated urine specimen from UUT with many degenerating desquamated intestinal epithelial cells to decrease the sensitivity of urine cytology. Many previous studies have attempted to identify several predictive risk factors of UUTR, however, their predictive values varied from those reported in other studies to remain controversial due to different characteristics of the enrolled patients [3], [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of upper tract recurrence following radical cystectomy for urothelial cancer ranges from 2% to 6% [3, 611], with the majority of recurrence in the first 3 years [3]. Additionally, Tran et al [3] demonstrated that the risk of upper tract recurrence does not change with time, emphasizing the critical importance of continued surveillance for UTTCC following cystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…14 The recurrence of UUT is associated with poor survival because metastases are often detected at the time of diagnosis. 15 After cystectomy, the patients are usually monitored by computed tomography (CT) and urine cytology, but the efficacy of this approach Tubeless umbilical cutaneous ureterostomy remains debatable. Urine cytology is considered an inadequate screening tool after radical cystectomy and ileal conduit because the test does not distinguish the cancer cells from degenerated intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%